Diagnosing the determinants of vaccine hesitancy in specific subgroups: The Guide to Tailoring Immunization Programmes (TIP). Issue 34 (14th August 2015) - Butler, Robb; MacDonald, Noni E.; the SAGE Working Group on Vaccine Hesitancy, 2
Abstract Despite relatively high vaccination coverage rates in the European Region, vaccine hesitancy is undermining individual and community protection from vaccine preventable diseases. At the request of its European Technical Advisory Group of Experts on Immunization (ETAGE), the Vaccine-preventable Diseases and Immunization Programme of the WHO Regional Office for Europe (WHO/EURO) developed tools to help countries address hesitancy more effectively. The Guide to Tailoring Immunization Programmes (TIP), an evidence and theory based behavioral insight framework, issued in 2013, provides tools to (1) identify vaccine hesitant population subgroups, (2) diagnose their demand- and supply-side immunization barriers and enablers and (3) design evidence-informed responses to hesitancy appropriate to the subgroup setting, context and vaccine. The Strategic Advisory Group of Experts on Immunization (SAGE) through its Working Group on Vaccine Hesitancy has closely followed the development, implementation, use and evolution of TIP concluding that TIP, with local adaptation, could be a valuable tool for use in all WHO regions, to help address countries' vaccine hesitancy problems. The TIP principles are applicable to communicable, noncommunicable and emergency planning where behavioral decisions influence outcomes.